Development of a Clean Energy-Based Information System for Mapping Marine Environmental Conditions and Navigational Safety to Support Sustainable Marine Tourism - Imam Sutrisno; Perwi Darmajanti; Irma Rustini; Endang Pudji Purwanti; Fahmi Umasangadji; Ardiansyah Ardiansyah; Heri Sutanto; Joko Subekti (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Marine tourism development requires accurate information regarding marine environmental conditions and navigational safety. However, many coastal tourism areas in Indonesia still rely on conventional observation methods that are limited, fragmented, and difficult to access in real time. This study aims to develop a clean energy-based information system capable of mapping marine environmental conditions and supporting navigational safety for sustainable marine tourism. The system integrates environmental sensors, Global Positioning System (GPS), Geographic Information System (GIS), and renewable energy sources through solar-powered monitoring stations. The research employed a Research and Development (R&D) method consisting of needs analysis, system design, prototype development, implementation, and evaluation. Data were collected from temperature, salinity, wave height, wind speed, water level, and vessel route monitoring. The resulting system provides spatial visualization, hazard alerts, route recommendations, and environmental status information through a web-based dashboard. The implementation results indicate that the system can improve the effectiveness of marine environmental monitoring and increase navigation safety in tourism areas. Furthermore, the use of solar energy supports sustainable operation in remote coastal locations with limited electricity access.